Lumped-kinetic modeling and experiments on co-pyrolysis of palm kernel cake with polystyrene using a closed-tubing reactor to upgrade pyrolysis products. (1st December 2021) - Vo, Thuan Anh; Ly, Hoang Vu; Tran, Quoc Khanh; Kwon, Byeongwan; Kim, Seung-Soo; Kim, Jinsoo
Graphical abstract: Highlights: Lumped-kinetic modeling for prediction of profile of product yields and kinetic parameters. Synergistic effect on activation energy and quality of oil derived from PKC/PS (80/20) blend. The O and N contents of bio-oil were decreased via the HDO and HDN reactions. Co-pyrolysis of PKC/PS increased yield, aromatic hydrocarbons content and HHV of bio-oil. Co-pyrolysis of PKC/PS improved properties of bio-char and non-condensable gases. Abstract: Lumped-kinetic modeling and experiments (with validation) were performed on palm kernel cake/polystyrene (PKC/PS) blend co-pyrolysis in a closed-tubing reactor. The lsqcurvefit function and ode solver defined in the Matlab software were properly applied to predict the profile of product yields and to determine exactly the kinetic parameters of the reactions involved in PKC/PS blend co-pyrolysis. The different iso-conversional methods based on thermogravimetric analysis were used to calculate the activation energy needed for thermal decomposition of PKC, PS, and the PKC/PS blend. A synergistic effect existed in the blend of PKC/PS (with 20 wt% PS) because its activation energy was lower than that of the individual materials. The co-pyrolysis not only improved the quantity but also the quality of the bio-oil product, providing a high proportion of aromatic hydrocarbons. The O and N contents of the bio-oil were reduced during co-pyrolysis via the hydrodeoxygenation and hydrodenitrogenation reactions. The highest heating value of the oil was 34.17 MJ/kg obtained in co-pyrolysis of PKC/PS at 773 K for 12 min. The co-pyrolysis increased the selectivity of H2 and hydrocarbon gases, and decreased the COx content. The biochar with high heating value and inorganic compounds content, and having a porous structure, can act as a catalyst and can be used as a solid fuel. This approach provides an efficient method for upgrading comprehensively the pyrolysis products using PS as the H2 -donor source.